Speech Acts And Their Implicatures In The Main Characters Of The Swimmers; A Film Directed By Sally El Hosaini - Fahreza, M. Naufal Rifa; Mahyuni, Mahyuni; Isnaini, Muhammad; Arifuddin, Arifuddin (Journal of Authentic Research, 2025)
This study investigates pragmatic features in the 2022 film The Swimmers, focusing on the speech acts and conversational implicatures employed by the main characters, Sara and Yusra Mardini. Addressing a gap in previous research that rarely combines these two frameworks within a single cinematic discourse, this study explores how language functions as a reflection of emotion, power, and social reality in the film. Using a qualitative approach, 30 utterances in 12 key descriptive scenes (approximately 45 minutes of dialogue) were analyzed based on Searle's speech act theory and Grice's conversational implicatures. The research findings reveal five types of speech acts: assertive, directive, commissive, expressive, and declarative, with assertive acts being the most frequent. Implicatures primarily emerge through violations of the maxims of quality and relation, which convey hidden meanings and emotional tension. The results highlight the crucial role of pragmatic strategies in establishing character identity and narrative depth. Pedagogically, this study demonstrates that film dialogue can serve as authentic material to enhance the pragmatic competence of English as a Foreign Language (EFL) learners, while also contributing to film studies by illustrating how cinematic language reflects real-world communication.